Hormesis Effect of Radon in Rats of the Krushinsky-Molodkina Line - Marine, Nikolaishvili; Zakharia, Nanobashvili; Nodar, Mitagvaria; Gvantsa, Chkadua; Irina, Bilanishvili; Ekaterine, Nozadze; T, Rtveladze; Tea, Museliani; Khatuna, Dondoladze; Gogi, Jikia (European Scientific Journal, ESJ, 2022)
According to this research, the use of radon inhalation in experimental animals, particularly in genetically determined rats with epileptic seizures, altered all parameters of the epileptic seizure development picture, namely the hidden period and the first and second wild jog duration after the audiogenic signal. On the third day, no response to the audiogenic signal was observed at all, and there was not even a single episode of tonic-clonic seizures. All what was mentioned suggests that radon inhalation can be used to treat epilepsy. This study is the first precedent of attempting R-Ho through inhalation for treatment of epileptic seizures in animal models with further translation to clinical study in humans through pilot phase II study. More profound and scientifically systematized approach is needed to determine the uniqueness of Tskhaltubo water springs, investigating the mechanisms of radon effects on the excitatory and inhibitory functioning of CNS, and the use of further clinical studies to establish its effectiveness on humans.